2015
DOI: 10.1167/15.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Temporal crowding and its interplay with spatial crowding

Abstract: Spatial crowding refers to impaired target identification when the target is surrounded by other stimuli in space temporal crowding refers to impaired target identification when the target is surrounded by other stimuli in time previously, when spatial and temporal crowding were measured in the fovea they were interrelated with amblyopic observers but almost absent with normal observers bonneh, sagi, & polat, 2007. In the current study we examined whether reliable temporal crowding can be found for normal obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 40 publications
4
41
3
Order By: Relevance
“…Another notable discrepancy is that the increase of impact near the last frame, which characterizes the recency effect, appears too steep in human data as compared to the model prediction. This might be partly owing to the visible persistence of the last frame 53 , backward masking of the previous frames by the last frame 54 , or temporal crowding, in rapid presentation 55,56 . However, it is doubtful that such perceptual effects can entirely explain our results because our subsequent experiments confirmed that such a steep recency effect is still robustly observed even if frame rate was reduced to as slow as 10 Hz and the average orientation of every frame (100 ms) was perceived very clearly.…”
Section: Discussionmentioning
confidence: 99%
“…Another notable discrepancy is that the increase of impact near the last frame, which characterizes the recency effect, appears too steep in human data as compared to the model prediction. This might be partly owing to the visible persistence of the last frame 53 , backward masking of the previous frames by the last frame 54 , or temporal crowding, in rapid presentation 55,56 . However, it is doubtful that such perceptual effects can entirely explain our results because our subsequent experiments confirmed that such a steep recency effect is still robustly observed even if frame rate was reduced to as slow as 10 Hz and the average orientation of every frame (100 ms) was perceived very clearly.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, known as visual crowding, has been extensively studied in the last two decades. Crowding is thought to be a major limiting factor of reading and of spatial vision although the precise nature of its underlying mechanisms is still strongly debated (He, Cavanagh, & Intriligator, 1996;Herzog, Sayim, Chicherov, & Manassi, 2015;Intriligator & Cavanagh, 2001;Pelli, Palomares, & Majaj, 2004;Pelli & Tillman, 2008;Saarela, Sayim, Westheimer, & Herzog, 2009;Strasburger, Harvey, & Rentschler, 1991;Strasburger & Malania, 2013;Tyler & Likova, 2007;Wolford, 1975;Yeshurun & Rashal, 2010;Yeshurun, Rashal, & Tkacz-Domb, 2015). Some recent reviews show the difficulty of providing a clear-cut understanding of crowding (Levi, 2008;Strasburger, Rentschler, & Jüttner, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Visual crowding occurs not only for stimuli that are in close spatial proximity, but also for stimuli that are temporally close to one another. Yeshurun, Rashal and Tkacz-Domb (2015) investigated temporal crowding for letters by varying presentation rate.…”
Section: Visual Crowdingmentioning
confidence: 99%